2006
DOI: 10.1111/j.1467-8535.2006.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of instructional elements in computer‐based instruction

Abstract: This study investigated the effects of several elements of instruction (objectives, information, practice, examples and review) when they were combined in a systematic manner. College students enrolled in a computer literacy course used one of six different versions of a computer-based lesson delivered on the web to learn about input, processing, storage and output of a computer. The six versions of the program consisted of (1) a full version that contained information plus objectives, practice with feedback, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 20 publications
4
33
0
3
Order By: Relevance
“…Izbrana učna enota v naši raziskavi je imela tudi nekaj elementov, ki jih kot potrebne navajata Gagné in Medsker (1996), npr. navezovanje na predznanje, usmerjanje dijakov, vaja, torej elemente, ki olajšujejo samostojno učenje dijakov Leow in Neo, 2014;Martin, Klein in Sullivan, 2004). Primernost izbranega e-učbenika so posredno potrdili tudi dijaki ES in KS, saj so navajali, da razumevanje učne snovi ni bilo zahtevno.…”
Section: Razpravaunclassified
“…Izbrana učna enota v naši raziskavi je imela tudi nekaj elementov, ki jih kot potrebne navajata Gagné in Medsker (1996), npr. navezovanje na predznanje, usmerjanje dijakov, vaja, torej elemente, ki olajšujejo samostojno učenje dijakov Leow in Neo, 2014;Martin, Klein in Sullivan, 2004). Primernost izbranega e-učbenika so posredno potrdili tudi dijaki ES in KS, saj so navajali, da razumevanje učne snovi ni bilo zahtevno.…”
Section: Razpravaunclassified
“…A foglalkozások során alkalmazhatunk olyan feladatokat, amelyek során a gyermek egyértelműen csak a gépre tud hagyatkozni, az utasításokat, feladatokat az eszköz révén kapja, vagy alkalmazhatjuk a számítógépet mint a foglalkozás menetét előre lendítő, a gyermeket motiváló, támogató eszközt. Az IKT-eszközök segítségével a probléma alapú tanulás is megjelenhet (Martin, Klein, & Sullivan, 2007), az óvodások számára akár játékosan modellezhető, animálható egy-egy gyakran előforduló élethelyzet, természeti folyamat. A feladatok során az egyéni munka mellett a kollaboratív munkaformát is megtapasztalhatja a gyermek (Badia, Meneses, & García, 2015).…”
Section: Az Ikt Felhasználási Lehetőségei Az óVodábanunclassified
“…For instance, research on effectiveness of objectives in computer-based cooperative learning reported that students who were exposed to the instructional objectives performed significantly better on posttest items than those who received either advanced organizers or no orientation activities (Klien & Cavalier, 1999), Researchers have also found that objectives do not produce significant difference in learning (Martin, Klien & Sullivan 2007). Hannafin (1987) reported that the presence of objectives systematically introduced into a computer-based instruction did not significantly influence performance in lessons presented.…”
Section: Objectivesmentioning
confidence: 99%